Riesgo de fractura del clavo intramedular en un espaciador tumoral para rodilla - Domínguez Hernández, Víctor Manuel; Araujo Monsalvo, Víctor Manuel; Silva Lomelí, José de Jesús; Rico Martínez, Genaro; Linares González, Luis Miguel; Delgado Cedillo, Ernesto (Revista Mexicana de Ingenieria Biomedica, 2003)
Bone tumors affects the knee in most of the cases. A new design of a spacer developed reported satisfactory results. In one case implant has broken due to a fall, in the distal hole of femur. Corresponding interlocking pin has not been inserted. The spacer has been implanted after resection of a malignant fibrous histiocitoma in a 85-years-old female patient. A finite-element model of femur-tibia-spacer was developed, including loads that are verified in gait cycles. Displacements obtained showed no significant difference. In the case where distal interlocking pin of femur was absent, stresses were 95% higher than those verified with pin present, and it was 83% higher without pin and when the bone was not drilled. When the distal pin was located 1-5 cm from spacer, stresses did not show any significant difference with respect to those case with pin at 0.5 cm. It was also studied one load set that reproduces a lateral fall, finding that stresses at distal pin hole were higher than the strength of stainless steel (1,100 MPa), for the case without pin (2,638 MPa), and with pin (1,388 MPa). For the mentioned above, it is clear that the implant was broken due to the absence of distal pin, when the patient fell.